Silvopasture and altitudinal gradient reduce heat stress in livestock production in the Peruvian tropics - Murga-Orrillo, Hipolito; Arévalo López, Luis Alberto; Mathios Flores, Marco Antonio; Cáceres Coral, Jorge; García, Melissa Rojas; Guerra Teixeira, Aldi Alida; Valderrama, Nilton Luis Murga (Frontiers in Animal Science, 2025)
In the Peruvian tropics, crossbreeding occurs between Bos taurus cattle, such as Brown Swiss (BS), Holstein (H), and Jersey (J), and Bos indicus cattle, such as Brahman (B) and Gyr (G). However, these cattle are exposed to high temperature humidity indices (THI). The aim was to evaluate variations in milk components, blood parameters of cows, and weight gain of calves in pasture-based production systems with mixed approaches along an altitudinal gradient. Six cows and six calves were evaluated at altitudes of 170, 503, 661, and 1110 m. Cattle experience higher heat stress in monoculture pasture areas; however, silvopastoral areas and altitudinal gradients mitigate this stress. The fat content in the milk of BSxJ cows showed significant differences (CI: 95%), with lower values; glucose and hemoglobin in their blood exhibited strong positive and negative correlations (p<0.05) with THI. At 661 m, the milk from GxH cows had higher values of fat, solids, density, protein, and salts, which were associated with better chemical properties of the pastures. Blood electrolytes Cl- and Na+ tended to be higher in BSxG cows, while Na+ levels were lower in GxH cows. However, red blood cells and hemoglobin were higher in GxH cows and lower in cows crossed with BS. In calves, the highest weight gains at lower altitudes were observed in BSxB crosses, while at higher altitudes, GxH crosses showed the greatest gains, likely associated with better production management.